2017
DOI: 10.1158/2326-6066.cir-16-0287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Acquired Resistance to Anti–PD-1 Therapy in Advanced Melanoma

Abstract: Anti–PD-1 therapy has improved clinical outcomes in advanced melanoma, but most patients experience intrinsic resistance. Responding patients can develop acquired resistance to anti–PD-1. We retrospectively reviewed 488 patients treated with anti–PD-1 from three academic centers and identified 36 patients with acquired resistance, defined as disease progression following objective response. The incidence, timing, disease sites, post-progression survival (PPS), and outcomes were evaluated descriptively. The acq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…A case series of acquired resistance to PD-1 axis inhibitors in 26 NSCLC patients found that a majority (89%) of these patients had recurrence limited to one or two sites of disease [ 7 ]. Isolated progression was also reported in the majority (78%) of 36 melanoma patients with acquired resistance to PD-1 blockade [ 29 ]. MMR-D patients under PD-1 blockade have been reported to develop acquired resistance, with tumors developing from occult sites such as the brain and the bone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of acquired resistance to PD-1 axis inhibitors in 26 NSCLC patients found that a majority (89%) of these patients had recurrence limited to one or two sites of disease [ 7 ]. Isolated progression was also reported in the majority (78%) of 36 melanoma patients with acquired resistance to PD-1 blockade [ 29 ]. MMR-D patients under PD-1 blockade have been reported to develop acquired resistance, with tumors developing from occult sites such as the brain and the bone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those patients who do respond to ICB, failure frequently occurs in sites of prior disease, with 60% of failures in anti-PD-1/PD-L1 treated NSCLC and 39% of failures in anti-PD-1 treated melanoma occurring in this way (Table 1). 42,43 Possible explanations include the importance of the activated T cell to tumor burden ratio in melanoma, 37 the existence of heterogeneous tumor-immune microenvironments in different metastatic lesions within a single patient, 44 and the presence of antigen loss variantsdcancer cells that have lost or mutated an antigen being targeted by cytotoxic T cellsdwithin bulk tumor populations. 45 Improved ICB response with decreased disease burden and failure in sites of gross disease point directly to the importance of effective ablation in this setting.…”
Section: Immunotherapy Response and Patterns Of Failurementioning
confidence: 99%
“…1). 37,64 The combination of preliminary clinical data that suggest a small clinical benefit of single-site radiation therapy plus ICB 52,53 and the predictable failure of ICB in sites of gross disease 42,43 with preclinical data by Zhang et al 66 that demonstrates local irradiation can lead to cytotoxic T cell mediated eradication of antigen loss variants leads directly to the theoretical importance of complete cytoreduction. However, the pivotal role of cytotoxic T cells and the importance of their ratio to tumor burden as outlined earlier highlight a potential limitation of this approach: if tumor-infiltrating lymphocytes are killed by irradiation, complete cytoreduction could amplify unwanted immunosuppressive effects.…”
Section: The Local Responsementioning
confidence: 99%
“…As in the study by Gettinger et al, 10 isolated progression was noted in the majority (78%) of the 36 patients with melanoma and was amenable to local therapy. 15 This report from the melanoma literature suggests the possibility of shared biological mechanisms of acquired resistance across cancer types.…”
mentioning
confidence: 92%